Effectiveness of Partial Wrapping of Stainless-Steel Wire Mesh on Compression Behavior of Concrete Cylinders (Fracture and Structural Integrity, 2024)
Partial confinement can provide sufficient reinforcement to enhance the compressive strength and ductility of concrete with lesser confining material. This paper presents the results of an axial compression test conducted on eighteen plain concrete cylinders of 150 mm diameter and 300 mm height partially confined with a Stainless-Steel Wire Mesh (SSWM) strip of different widths. The study included two specimens without wrapping, two fully wrapped specimens, and others wrapped with two SSWM strips of varying widths at both the ends of concrete cylinder. The strain on SSWM up to failure is measured to understand the effectiveness of lateral confining pressure on the behaviour of concrete cylinders. The peak axial compressive strength and corresponding strain of unconfined and SSWM-confined concrete cylinders are compared. The result shows a significant increase in peak confined compressive stress as compared to an unconfined concrete cylinder. However, the confinement efficiency is reduced when the height of the unconfined region exceeds the diameter of the cylinder, and significant strain localisation is detected within the unwrapped region. Based on experimental investigation, a confinement coefficient is suggested for a partial wrapping of SSWM on the concrete cylinder.
Keywords: Compression behaviour; Partial wrapping; Stainless Steel Wire Mesh; Concrete cylinder; Confinement coefficient